Oligopeptide transporter PepT1 in Atlantic cod (Gadus morhua L.): cloning, tissue expression and comparative aspects - Rønnestad, I. (2014)
A novel full-length cDNA that encodes for the Atlantic cod (Gadus morhua L.) PepT1-type oligopeptide transporter has been cloned. This cDNA (named codPepT1) was 2838·bp long, with an open reading frame of 2190·bp encoding a putative protein of 729 amino acids. Comparison of the predicted Atlantic cod PepT1 protein with zebrafish, bird and mammalian orthologs allowed detection of many structural features that are highly conserved among all the vertebrate proteins analysed, including (1) a larger than expected area of hydrophobic amino acids in close proximity to the N terminus; (2) a single highly conserved cAMP/cGMP-dependent protein kinase phosphorylation motif; (3) a large N-glycosylationrich region within the large extracellular loop; and (4) a conserved and previously undescribed stretch of 8–12 amino acid residues within the large extracellular loop. Expression analysis at the mRNA level indicated that Atlantic cod PepT1 is mainly expressed at intestinal level, but that it is also present in kidney and spleen. Analysis of its regional distribution along the intestinal tract of the fish revealed that PepT1 is ubiquitously expressed in all segments beyond the stomach, including the pyloric caeca, and through the whole midgut. Only in the last segment, which included the hindgut, was there a lower expression. Atlantic cod PepT1, the second teleost fish PepT1-type transporter documented to date, will contribute to the elucidation of the evolutionary and functional relationships among vertebrate peptide transporters. Moreover, it can represent a useful tool for the study of gut functional regionalization, as well as a marker for the analysis of temporal and spatial expression during ontogeny.